THE EVOLUTION OF HUYULA VALUES AS A FORM OF SOCIAL CAPITAL TO STRENGTHEN SOLIDARITY AND CULTURAL IDENTITY IN THE MODERN ERA - Bouzina, Imane M’hammedi; Yunus, Rasid (Universitas Negeri Gorontalo, 2025)
This study seeks to explore the significance of Huyula as a form of social capital that contributes to enhancing solidarity, social cohesion, and cultural identity among the residents of Polohungo Village. It also aims to identify the challenges faced in preserving these values amidst social change and modernization. The research employs a qualitative methodology, utilizing data collection techniques such as in-depth interviews with community leaders and the younger generation, participatory observation in communal work activities, and documentation of social events in the village. The findings reveal that the values of Huyula remain vibrant and serve as a crucial foundation for fostering unity, altruistic mutual assistance, and informal conflict resolution grounded in cultural norms. Indigenous leaders, religious figures, and village women play a pivotal role in upholding and transmitting these values. However, the advent of digital technology, shifts in the lifestyle of the younger generation, and the rise of individualism pose significant threats to the continuity of Huyula's values. Innovations by the younger generation, using social media as a platform for documenting and promoting cooperative activities, present opportunities for a dynamic and adaptive cultural revitalization. Based on these insights, the research suggests the formal integration of Huyula values into village policies, the enhancement of community empowerment programs rooted in local wisdom, and the regular organization of cultural festivals as efforts to sustain the presence and relevance of Huyula values within the framework of sustainable social development